2022
DOI: 10.32479/ijeep.13132
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Oil Prices on the Macroeconomic Indicators of Kazakhstan and the Consequences for the Formation of Social Policy

Abstract: The article analyzes the impact of the dynamics of oil prices on the main macroeconomic indicators of the Kazakhstani economy and the consequences of the formation of national social policy. The article applies different hypotheses about the sensitivity of macroeconomic indicators of the economy of Kazakhstan to fluctuations of oil prices, and in addition, it specifies and evaluates a system of simultaneous equations that allows to test these hypotheses. Scenarios for the reaction of the Kazakhstani economy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Thus, an effective information system improves coordination. Effective marketing of products in rural areas and flexible logistics systems are also considered essential factors in achieving marketing objectives (Moldabekova et al, 2022). All these factors mentioned by the researchers in their study should also be considered by entrepreneurs in Kazakhstan when forming long-term development strategies.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, an effective information system improves coordination. Effective marketing of products in rural areas and flexible logistics systems are also considered essential factors in achieving marketing objectives (Moldabekova et al, 2022). All these factors mentioned by the researchers in their study should also be considered by entrepreneurs in Kazakhstan when forming long-term development strategies.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, an effective information system improves coordination. Effective marketing of products in rural areas and flexible logistics systems are also considered essential factors in achieving marketing objectives (Moldabekova et al, 2022). All these factors mentioned by the researchers in their study should also be considered by entrepreneurs in Kazakhstan when forming long-term development strategies.…”
Section: Discussionmentioning
confidence: 96%
“…At the same time, based on the results obtained, it was determined that fluctuations in world oil prices have a significant impact on real GDP, consumer price index and inflation rate, interest rate and exchange rate. Moldabekova et al (2022), one of the studies of the recent period, also analyzed the impact of fluctuations in world oil prices on the main macroeconomic indicators of Kazakhstan and social policy and concluded that these fluctuations are very effective.…”
Section: Studies Covering New Oil Statesmentioning
confidence: 99%